P12 Risk factors for failure of bilateral sentinel lymph node mapping in early-stage cervical cancer. (1st November 2019) - Bresset, A; Balaya, V; Guani, B; Magaud, L; Bonsang-Kitzis, H; Deloménie, M; Nguyen-Xuan, H-T; Koual, M; Montero Macias, R; Ngo, C; Bats, A-S; Mathevet, P; et al.
Abstract : Introduction/Background: The objective of this study was to determine clinical, tumor and surgical factors associated with sucessful bilateral sentinel lymph node mapping (SBM) in early-stage cervical cancer. Methodology: We performed an ancillary work on the data of two prospective trials on SLN biopsy (SENTICOL I & II). Patients having lymph node dissection for FIGO IA-IIA cervical cancer were included between 2005 and 2012 from 25 French oncologic centers. Sentinel lymph node (SLN) was detected by a combined labeling technique (blue and isotopic). Results: 405 patients were included for analysis: SLNs were identified on at least one side of the pelvis in 381 patients (94.1%) and bilaterally in 326 patients (80.5%). No SLNs were found in 24 patients (6%). The mean age was 43 years [22–85 years]. Most patients (88.1%) had IB1 clinical FIGO stage. The majority of patients (71%) had squamous cells carcinoma. Surgeries were mainly performed by mini-invasive approach (368 patients - 90.9%). By multivariate analysis, SBM was associated with inclusion during the period 2009–2012 (ORa=2.24, 95%CI = [1.09–4.61], p=0.03) compared to the period 2005–2007. Failure of bilateral SLN mapping was associated with Age ≥ 70 years (ORa=0.02, 95%CI = [0.002–0.29], p=0.003), BMI >30 kg/m 2 (ORa= 0.33, 95%CI = [0.15–0.75], p=0.01) and tumor size ≥ 20 mm (ORa=0.41, 95%CI = [0.19–0.87], p=0.02) Conclusion: A better experience of SLN biopsy technique improved SBM rate in early-stage cervical cancer. Age higher than 70 years, obesity and tumor larger than 20 mm decreased siignificantly SBM. Disclosure: Nothing to disclose.